2013
DOI: 10.1186/1475-2867-13-70
|View full text |Cite
|
Sign up to set email alerts
|

Localization of BRCA1 protein in breast cancer tissue and cell lines with mutations

Abstract: BackgroundThe breast and ovarian cancer susceptibility gene (BRCA1) encodes a tumor suppressor. The BRCA1 protein is found primarily in cell nuclei and plays an important role in the DNA damage response and transcriptional regulation. Deficiencies in DNA repair capabilities have been associated with higher histopathological grade and worse prognosis in breast cancer.MethodsIn order to investigate the subcellular distribution of BRCA1 in tumor tissue we randomly selected 22 breast carcinomas and tested BRCA1 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…However, BRCA1 mutation screening is helpful only for individuals who receive a clear-cut result (pathogenic mutation with a known function or negative for any mutation) and not for others who have BRCA1 mutations with uncertain significance. Our data indicated that BRCA1 expression and subcellular localization might stand as an independent prognostic factor in breast cancer which is supported by similar findings from previous studies [ 17 , 23 , 38 ]. However, this research would benefit greatly from larger population-based studies that might encourage health care workers to incorporate BRCA1 staining in breast cancer prognosis algorithm.…”
Section: Discussionsupporting
confidence: 92%
“…However, BRCA1 mutation screening is helpful only for individuals who receive a clear-cut result (pathogenic mutation with a known function or negative for any mutation) and not for others who have BRCA1 mutations with uncertain significance. Our data indicated that BRCA1 expression and subcellular localization might stand as an independent prognostic factor in breast cancer which is supported by similar findings from previous studies [ 17 , 23 , 38 ]. However, this research would benefit greatly from larger population-based studies that might encourage health care workers to incorporate BRCA1 staining in breast cancer prognosis algorithm.…”
Section: Discussionsupporting
confidence: 92%
“…We confirmed the low, cytosolic expression of BRCA1 in HCC1937 while in HCC1937/wt BRCA1, the BRCA1 protein was expressed and localized specifically to the nucleus (Additional file 3 : Figure S2). This was expected as the truncated, non-functional BRCA1 expressed by HCC1937 has been observed in nucleus as well as the cytoplasm [ 32 ]. Cell proliferation assay revealed that PB is highly selective towards the HCC1937 cells with 5 μM concentration inhibiting proliferation in 56 % cells while in HCC1937/wt BRCA1 only 25 % inhibition of proliferation was observed (Fig.…”
Section: Resultsmentioning
confidence: 94%
“… 25 AMJ13 cells were positive for BRCA1 nuclear staining, but to a lesser degree than for BRCA2, which was positive for both nuclear and cytoplasmic staining. Tulchin et al 26 frequently found reduced BRCA1 nuclear staining in breast tumor tissue when compared with normal tissue, and less BRCA1 staining with higher histological tumor grade. Strong positive staining of the nucleus and cytoplasm suggests mutation in BRCA1 because of its role in cell cycle control and DNA repair.…”
Section: Discussionmentioning
confidence: 99%